Answer:
x = -17/2 - sqrt(15/2)/2 or x = sqrt(15/2)/2 - 17/2
Step-by-step explanation:
Solve for x:
30 = (-4 x - 34)^2
30 = (-4 x - 34)^2 is equivalent to (-4 x - 34)^2 = 30:
(-4 x - 34)^2 = 30
Take the square root of both sides:
-4 x - 34 = sqrt(30) or -4 x - 34 = -sqrt(30)
Add 34 to both sides:
-4 x = 34 + sqrt(30) or -4 x - 34 = -sqrt(30)
Divide both sides by -4:
x = -17/2 - sqrt(15/2)/2 or -4 x - 34 = -sqrt(30)
Add 34 to both sides:
x = -17/2 - sqrt(15/2)/2 or -4 x = 34 - sqrt(30)
Divide both sides by -4:
Answer: x = -17/2 - sqrt(15/2)/2 or x = sqrt(15/2)/2 - 17/2